"The laughing third man in a fight": Stalin's use of the wedge strategy. Issue 1 (March 2017) - Hager, Robert P.
Abstract: Although much IR theory focuses on balancing, this paper examines a version of the wedge strategy, what Stalin allegedly called being "the laughing third man in a fight." This is the practice of advancing one's goals by setting up other states to fight each other. The first case study is Soviet strategy in Europe from September 1939 until June 1941. The second is Soviet strategy in the Far East in 1941–45. What I am looking at here is a policy of deliberately encouraging the start of a war and/or aiding its prolongation in order to weaken both sides. The two case studies indicate that the Soviet Union used such a strategy at times in place of the usual forms of balancing, discussed in the international relations literature. Additionally, analysis of Moscow's conduct, statements by Soviet leaders, and the policies of a number of foreign communist parties indicate that, in addition to any security goals, Stalin's agenda included furthering the USSR's goal as a revolutionary state, even thought this had at times to be constrained by realpolitik.